ACTIVE FRACTIONS FROM E. COLI ATCC 35218 WITH ANTIMICROBIAL AND ANTIOXIDANT PROPERTIES - M. Maqsood; Z. Mushtaq; Kashif Jilani; U. Khan (Journal of Animal and Plant Sciences, 2019)
Discovery of new therapeutic agents has become crucial because mankind is experiencing issues regarding health and environment. In the current study Escherichia coli (ATCC 35218) extracts were evaluated for their antimicrobial and antioxidant potentials against different bacterial and fungal species. Different extracts were prepared following different methods including soxhlet extraction with ethanol using cell mass of E. coli. Some other extracts like crude proteins, crude isoprenoid quinine and polar lipids were extracted from the E. coli cell mass with different extraction solvents. Another extraction was done using solvents in order of increasing polarity by using methanol as well as n-hexane, chloroform, ethyl acetate and water. The antimicrobial potential was evaluated by well diffusion as well as disc diffusion method. The antioxidant effect of E. coli extracts were investigated in terms of DPPH free radical scavenging activity. Polar lipids showed maximum antibacterial activity in a range of 5-9 mm against Bacillus subtilis, Staphylococcus aureus and Pasturella multocida. Extract of Crude proteins exhibited maximum antioxidant activity (83.45%). A significant antifungal activity of about 13 mm against Fusarium solani was also shown by crude polar lipids. Finally, results were analyzed statistically by the paired t-test (Tucky’s test) using software Statistix, version 8.1.
Keywords: Bioactive compounds; Escherichia coli; Antimicrobial potential; Ampicillin; Ciprofloxacine